Identifikasi Jamur Genus Aspergillus pada Gaplek di Kabupaten Gunung Kidul - H. A. Oramahi; Christanti Sumardiyono; Nursamsi Pusposendjojo; Haryadi Haryadi (Universitas Gadjah Mada, 2006)
The study was carried out in Gunung Kidul Regency of Yogyakarta special. Dried cassava was taken from the district of Nglipar (north zone), Wonosari (center zone), Semanu and Rongkop (south zones) for identification of the genera of Aspergillus growing on the samples. Clasification of the zones was based on the degree of rainfall on the area. Dichloran 18% Glyserol Agar (DG-18) medium was used for isolating pathogen, while Czapek Yeast Extract Agar (CYA), Czapek Yeast Extract Agar with 20% sucrose (CYA 20S) and Malt Extract Agar (MEA) media were used for identification. The fungi were identified on the basis of both macroscopic and microscopic morphologies. The result showed that The Genera Of Aspergillus growing on dry cassava were A. flavus, A. niger, A. oryzae, A. foetidus, A. zonatus and A. tamarii. A. flavus was a predominant fungus that grow on dry cassava.